The Myth of “Shikata Ga Nai:” The Japanese-American Community of Bainbridge Island, 1941-42 - Havera, Freddie (My University, 2026)
From the 1920s onward, the U.S. government planned to incarcerate Japanese-Americans in the event of a war with Japan. Once hostilities between the two countries broke out, federal authorities imprisoned Japanese immigrants in order to destabilize the Japanese-American community. Then the U.S. government removed all people of Japanese descent from the West Coast. Most of whom were confined in remote concentration camps, while others fled their homes. In the time since, people of Japanese descent have often described their attitude towards incarceration with the Japanese term “shikata ga nai,” which translates to “it cannot be helped.” However, historians have misinterpreted “shikata ga nai” to portray the incarcerees as passive subjects of state violence. This project centers on the Japanese-Americans of Bainbridge Island, who were the first community the government imprisoned during the war. It focuses on how they exercised their agency through various methods in an effort to avoid being incarcerated. Between the outbreak of war and the day the U.S. Army removed the Bainbridge Islanders from their homes, they affirmed their loyalty to America, joined the army, cooperated with the authorities, and tried to negotiate with the government. Through these actions, the Islanders attempted to achieve inclusion by proving that they deserved to live in America.
Bachelor of Arts (BA)
Keywords: Japanese American incarceration; Bainbridge Island; World War Two; state violence; shikata ga nai; concentration camps